A low-temperature resistant all-gel flexible supercapacitor with strong interface bonding performance and its preparation method and application

By using materials such as silver lignin nanoparticles to prepare all-gel flexible supercapacitors, the problem of reduced flexibility and electrochemical performance at low temperatures is solved, high flexibility and fatigue resistance are achieved, and the low-temperature performance of flexible energy storage systems is improved. Adaptability.

CN117976425BActive Publication Date: 2025-01-24INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311871435.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-01-24
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

The existing full-gel supercapacitors have reduced flexibility and electrochemical performance at low temperatures, and insufficient interface adhesion leads to interlayer sliding or layer delamination.

Method used

Using silver -wood quality nano -particle particles, nano hydroxyl phosphorus, acrylamide, and carbon nanoma, mix in supraultic water to form anterior cluster, and then add linked agents, cause and zinc chloride to form aggregation form formation form The hydrogel electrode and electrolyte are used to form a full gel flexible super capacitor through the in -situ aggregation.

Benefits of technology

The high flexibility and anti -fatigue performance of the full gel supercapacitors under low temperature conditions, maintaining high elastic response rates and reincarnation, and good electrochemical performance, improved the adaptability of the flexible energy storage system at low temperature Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117976425B_ABST
    Figure CN117976425B_ABST
Patent Text Reader

Abstract

The present invention discloses a low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion performance, and a preparation method and application thereof. The all-gel supercapacitor has a traditional electrode|electrolyte|electrode three-layer structure, has a high-toughness electrolyte / electrode interface, and at the same time, under low temperature conditions, still has good flexibility and fatigue resistance, and still maintains high elastic recovery rate and resilience after 1000 stretching cycles, and has good electrochemical properties. The preparation strategy of this all-gel supercapacitor improves the low-temperature adaptability of the flexible energy storage system at the device level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of capacitors, and in particular relates to a low-temperature resistant all-gel flexible supercapacitor with strong interface bonding performance, and a preparation method and application thereof. Background Art

[0002] Hydrogel matrices are becoming increasingly attractive due to their unique advantages, including intrinsic flexibility, environmental friendliness, and flame retardancy.

[0003] At present, most of the reported all-gel supercapacitors are prepared by sandwiching a hydrogel electrolyte between two hydrogel electrodes to form a three-layer structure. The similar mechanical properties between the electrodes and the electrolyte enable the supercapacitor to withstand certain deformations, such as bending, stretching, twisting and folding. However, there are still two major limitations in the assembly process of all-gel supercapacitors: First, due to the high water content on the hydrogel surface, the interfacial adhesion between the electrode and the electrolyte will be weakened, resulting in poor interfacial contact. Therefore, the all-gel supercapacitor may experience interlayer sliding or irreversible layer delamination during dynamic deformation;

[0004] Secondly, the solvent water in the hydrogel matrix will inevitably freeze at subzero temperatures, thereby reducing the flexibility and electrochemical performance of all-gel supercapacitors at low temperatures.

[0005] Therefore, the development of freeze-resistant all-gel supercapacitors without sacrificing their mechanical flexibility is highly anticipated for practical applications. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion performance.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion performance, comprising:

[0010] Adding a 5 wt.% alkali lignin aqueous solution dropwise into a 0°C silver ammonia solution containing 1.5 wt.% silver nitrate, and standing for 1 to 2 hours in the dark to obtain a silver lignin nanoparticle dispersion;

[0011] The silver lignin nanoparticle dispersion, nanohydroxyapatite and acrylamide are ultrasonically mixed in deionized water to obtain a precursor;

[0012] Adding a crosslinking agent, an initiator and a carbon nanotube dispersion to the prepolymer, polymerizing at room temperature for 10 to 12 hours to obtain a silver lignin / hydroxyapatite-polyacrylamide-carbon nanotube hydrogel;

[0013] The prepared hydrogel is immersed in a 0.5 mol / kg pyrrole solution, placed at 4°C for 1 to 3 hours, immersed in a 0.5 mol / kg ferric chloride solution for 1 to 3 hours, and dried until the water content of the hydrogel electrode is 40 to 50%, thereby obtaining a silver lignin / hydroxyapatite-polyacrylamide-carbon nanotube / polypyrrole hydrogel electrode;

[0014] A cross-linking agent, an initiator and zinc chloride are added to the precursor to obtain a prepolymer of a hydrogel electrolyte;

[0015] The prepolymer of the hydrogel electrolyte is poured on the hydrogel electrode, polymerized at room temperature for 2 to 5 minutes, and then another hydrogel electrode is attached and polymerized at room temperature for 10 to 12 hours to obtain a fully gel flexible supercapacitor.

[0016] As a preferred embodiment of the preparation method of the present invention, the average size of the silver lignin nanoparticles in the silver lignin dispersion is 100 to 1000 nanometers.

[0017] As a preferred embodiment of the preparation method of the present invention, in the precursor, the mass ratio of nano-hydroxyapatite to acrylamide is 1:5, and the mass ratio of the silver lignin nanoparticle dispersion to acrylamide is 1:2.

[0018] As a preferred embodiment of the preparation method of the present invention, a crosslinking agent, an initiator and a carbon nanotube dispersion are added to the prepolymer, wherein the mass ratio of the crosslinking agent to the acrylamide monomer is 3:1000, the mass ratio of the initiator to the acrylamide monomer is 3:250, and the mass ratio of the carbon nanotube to the acrylamide monomer is 1:5.

[0019] As a preferred embodiment of the preparation method of the present invention, the cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is any one of ammonium persulfate, potassium persulfate and sodium persulfate.

[0020] As a preferred embodiment of the preparation method of the present invention, a crosslinking agent, an initiator and zinc chloride are added to the precursor to obtain a prepolymer of a hydrogel electrolyte, wherein the mass ratio of the crosslinking agent to the acrylamide monomer is 3:1000, the mass ratio of the initiator to the acrylamide monomer is 3:500, and the mass ratio of the acrylamide monomer to the zinc chloride is 1:5.

[0021] As a preferred embodiment of the preparation method of the present invention, the cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is any one of ammonium persulfate, potassium persulfate and sodium persulfate.

[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide a low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion performance.

[0023] Another object of the present invention is to overcome the deficiencies in the prior art and provide a low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion for use in a flexible energy storage system.

[0024] Beneficial effects of the present invention:

[0025] In view of the defects of the all-gel flexible supercapacitor, the present invention provides a novel all-gel flexible supercapacitor with good interface toughness and antifreeze performance and a preparation method thereof. The all-gel supercapacitor has a traditional electrode|electrolyte|electrode three-layer structure, has a high-toughness electrolyte / electrode interface, and at the same time, under low temperature conditions, still has good flexibility and fatigue resistance, maintains high elastic recovery rate and resilience after 1000 stretching cycles, and has good electrochemical properties. This preparation strategy of the all-gel supercapacitor improves the low-temperature adaptability of the flexible energy storage system in the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0027] Figure 1 The scanning electron microscope (SEM) and energy dispersive x-ray spectroscopy (EDS) element mapping diagrams of the all-gel supercapacitor in Example 2 of the present invention are shown.

[0028] Figure 2: This is a performance test diagram of the all-gel supercapacitor in Example 2 of the present invention, wherein a is the tensile stress and strain curve of the all-gel supercapacitor at 1000 stretching cycles at 30% strain at 20, -20, -40 and -60°C; b is the charge and discharge curve of the all-gel supercapacitor in the temperature range of 20 to -40°C; c is the current density of 1 mA / cm 2 d is the discharge capacitance of the all-gel supercapacitor at temperatures ranging from 20°C to –40°C; d is the Nyquist plot of the temperature dependence of the all-gel supercapacitor, and the solid line corresponds to the fitted equivalent circuit; e is the cycling performance of the all-gel supercapacitor at 20°C and –40°C; f is the force and strain curves of the all-gel supercapacitor under 20% strain and subjected to 2000 stretching cycles at 20, –20 and –40°C; g is the charge and discharge curves of the all-gel supercapacitor under 20% strain and 2000 stretching cycles at different temperatures; h is the corresponding changes in the discharge specific capacitance of the all-gel supercapacitor when subjected to cyclic tension at different temperatures. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] The source of alkali lignin in the embodiment of the present invention is Aladdin;

[0033] The source of nano-hydroxyapatite is Aladdin, ≥97%, <100nm particle size;

[0034] The source of acrylamide monomer was Aladdin, AR, 99.0%.

[0035] Example 1

[0036] A method for preparing a hydrogel electrode with excellent flexibility and conductivity, the main steps are:

[0037] (1) In a 50 mL stirred reactor, 1 g of alkali lignin was dissolved in 20 mL of distilled water, stirred for 15 minutes, and then ultrasonicated for 5 minutes to fully dissolve the alkali lignin in the aqueous solution;

[0038] Dissolve 0.3 g of silver nitrate in 20 mL of distilled water, stir for 15 minutes, then add ammonia water dropwise until the solution becomes clear to obtain a silver ammonia solution;

[0039] Then the silver ammonia solution was placed in a 0°C ice water bath, the lignin dispersion was added dropwise thereto, and the solution was allowed to stand for 1 hour away from light to obtain a silver lignin nanoparticle dispersion;

[0040] (2) Add 2.52 g of nano-hydroxyapatite, 12.6 g of acrylamide monomer, 6.3 g of silver lignin nanoparticle dispersion, and 25.2 g of 10 wt.% carbon nanotube dispersion (Xianfeng Nano, XFM16 dispersion, concentration 10%, water) to 34.8 g of distilled water, stir at room temperature for 2 hours to fully dissolve, and ultrasonicate for 10 minutes to evenly disperse the hydroxyapatite and remove bubbles;

[0041] (3) Then, 37.8 mg of cross-linking agent N,N'-methylenebisacrylamide and 202.4 mg of ammonium persulfate were added, stirred in an ice-water bath for 30 minutes to fully dissolve, poured into a 10×10 mm square plastic dish with a thickness of 3 mm, and cross-linked and polymerized at room temperature for 12 hours to obtain silver lignin / hydroxyapatite-polyacrylamide-carbon nanotube hydrogel;

[0042] (4) The prepared hydrogel was immersed in 500 ml of 0.5 mol / kg pyrrole solution, placed at 4°C for 3 hours, and then immersed in 500 ml of 0.5 mol / kg ferric chloride solution for 3 hours to obtain a silver lignin / hydroxyapatite-polyacrylamide-carbon nanotube / polypyrrole hydrogel electrode;

[0043] (5) Finally, the hydrogel electrode was placed in a 40°C oven to dehydrate for 6 hours, and turned over every half an hour. The final moisture content of the hydrogel electrode was 30%, and the preparation of two gel electrodes was completed.

[0044] Example 2

[0045] Preparation of all-gel flexible supercapacitors:

[0046] In a 50 mL stirred reactor, 1 g of alkali lignin was dissolved in 20 mL of distilled water, stirred for 15 minutes and then ultrasonicated for 5 minutes to fully dissolve the alkali lignin in the aqueous solution;

[0047] Dissolve 0.3 g of silver nitrate in 20 mL of distilled water, stir for 15 minutes, then add ammonia water dropwise until the solution becomes clear to obtain a silver ammonia solution, then put the silver ammonia solution into a 0°C ice water bath, add the lignin dispersion dropwise thereto, and stand in dark for 1 hour to obtain a silver lignin nanoparticle dispersion;

[0048] Add 1.26 g of nano-hydroxyapatite, 6.3 g of acrylamide monomer, 3.15 g of silver lignin nanoparticle dispersion and 8.16 g of zinc chloride to 30 g of distilled water, stir for 2 hours at room temperature to fully dissolve them, and ultrasonicate for 10 minutes to evenly disperse the hydroxyapatite and remove bubbles;

[0049] Then, 18.9 mg of a cross-linking agent, N,N'-methylenebisacrylamide, and 75.6 mg of ammonium persulfate were added, and stirred in an ice-water bath for 30 minutes to fully dissolve the mixture, thereby obtaining a prepolymer of a hydrogel electrolyte;

[0050] A semi-dehydrated gel electrode prepared in Example 1 was placed in a 10×10 mm square plastic dish, and the prepolymer of the hydrogel electrolyte was poured into it with a thickness of about 2 mm. After polymerizing at room temperature for 5 minutes, another semi-dehydrated gel electrode was attached, and finally polymerized at room temperature for 12 hours to obtain a fully gel flexible supercapacitor.

[0051] Scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS) elemental mapping of the all-gel supercapacitor can be found in Figure 1 .

[0052] Example 3

[0053] Low temperature fatigue resistance of all-gel flexible supercapacitors:

[0054] The fatigue resistance of the all-gel supercapacitor was tested using an electronic universal testing machine and a high and low temperature chamber.

[0055] The (electrode|electrolyte|electrode) supercapacitor prepared in the above Example 2 was cut into a rectangular parallelepiped with a size of 50 mm×20 mm, and then the sample was vertically loaded between two stretching clamps with a distance between the two clamps fixed at 10 mm. A uniaxial stretching and recovery with a strain of 30% was applied in the vertical direction. A uniaxial stretching force was applied in the vertical direction with a strain loading rate of 50 mm / min. The number of continuous stretching-recovery times was 1000 times in total.

[0056] The stress-strain curve of the all-gel supercapacitor was obtained, and the stress reduction rate, plastic deformation rate and energy loss coefficient were calculated, such as Figure 2 As shown in Figure 1, even when the temperature drops to –60 °C, the all-gel supercapacitor can still withstand multiple stretching cycles without fatigue damage, maintaining a high elastic recovery rate of 86% and a high elastic recovery rate of ∼50% after 1000 stretching cycles.

[0057] Example 4

[0058] Low-temperature electrochemical performance of all-gel flexible supercapacitors:

[0059] The electrochemical performance of the all-gel supercapacitor at low temperature was tested using an ultra-low temperature refrigerator and an electrochemical workstation.

[0060] The full gel supercapacitor in Example 2 was cut into a 30 mm × 15 mm rectangle using silicone rubber, and two platinum current collectors and the full gel supercapacitor were encapsulated in an integrated device using silicone rubber. Cyclic charge and discharge tests were performed on the device with a voltage window of 0 to 0.8 V, and electrochemical impedance spectroscopy tests were performed with a frequency of 1 -2 ~10 5 , and calculate the changes in specific capacitance, energy density and power density at different temperatures and the cycle life.

[0061] like Figure 2 As shown in Fig. ac, the all-gel supercapacitor exhibits excellent capacitance performance in the temperature range of 20°C to –40°C, with the combined advantages of good ion transport in the electrolyte, stable charge transfer at the electrolyte / electrode interface, and effective ion diffusion in the electrode.

[0062] like Figure 2 d, at –40°C it has 11 mWh / cm 2 The high energy density and excellent cycle stability (average Coulombic efficiency is 98.1% and capacitance retention is 99.1% after 5000 cycles) are achieved.

[0063] Example 5

[0064] Stability of all-gel flexible supercapacitors under low-temperature dynamic deformation:

[0065] The stability of the all-gel flexible supercapacitor under low-temperature dynamic deformation was tested using an electronic universal testing machine and a high and low temperature chamber.

[0066] The all-gel supercapacitor prepared in Example 2 was cut into a cuboid of 25 mm × 15 mm in size, and then the sample was vertically loaded between two stretching clamps, and a platinum sheet was used as a current collector to assemble an integrated device and clamped between the two clamps, with a fixed distance of 15 mm. A uniaxial stretching and recovery with a strain of 20% was applied in the vertical direction, and the strain loading speed was 50 mm / min. Continuous stretching-recovery was performed to obtain the relationship between the cyclic stress and strain of the all-gel supercapacitor under 20% strain and the electrochemical stability in this process;

[0067] like Figure 2As shown by eh, the device can withstand dynamic deformation and maintain high capacitance retention after 2000 tensile cycles in the temperature range of 20 to –40 °C without delamination and electrochemical failure.

[0068] The present invention proposes a novel all-gel flexible supercapacitor with good interface toughness and antifreeze performance and a preparation method thereof. The prepolymer is obtained by mixing a lignin nanoparticle dispersion and acrylamide, nano-hydroxyapatite, a crosslinking agent, and an initiator in deionized water. A carbon nanotube dispersion / polypyrrole is introduced to polymerize at room temperature to form a hydrogel electrode, which loses 50% of water at 40°C. A hydrogel electrolyte prepolymer obtained by introducing zinc chloride is poured on a semi-dehydrated electrode and polymerized in situ at room temperature. The hydrogel electrolyte is simultaneously polymerized in situ on two electrodes to form a topological entanglement with two pre-existing networks, thereby obtaining an all-gel flexible supercapacitor with excellent electrolyte / electrode interface toughness. At the same time, the supercapacitor still has good flexibility and fatigue resistance at -60°C, maintains a high elastic recovery rate and resilience after 1000 stretching cycles, and has good electrochemical performance. The preparation strategy of the all-gel supercapacitor improves the low-temperature adaptability of the flexible energy storage system at the device level.

[0069] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion performance, characterized in that: include, Adding a 5 wt.% alkali lignin aqueous solution dropwise into a 0°C silver ammonia solution containing 1.5 wt.% silver nitrate, and standing for 1 to 2 hours in the dark to obtain a silver lignin nanoparticle dispersion; The silver lignin nanoparticle dispersion, nanohydroxyapatite and acrylamide are ultrasonically mixed in deionized water to obtain a precursor; Adding a crosslinking agent, an initiator and a carbon nanotube dispersion to the prepolymer, polymerizing at room temperature for 10 to 12 hours to obtain a silver lignin / hydroxyapatite-polyacrylamide-carbon nanotube hydrogel; The prepared hydrogel is immersed in a 0.5 mol / kg pyrrole solution, placed at 4°C for 1 to 3 hours, immersed in a 0.5 mol / kg ferric chloride solution for 1 to 3 hours, and dried until the water content of the hydrogel electrode is 40 to 50%, thereby obtaining a silver lignin / hydroxyapatite-polyacrylamide-carbon nanotube / polypyrrole hydrogel electrode; A cross-linking agent, an initiator and zinc chloride are added to the precursor to obtain a prepolymer of a hydrogel electrolyte; The prepolymer of the hydrogel electrolyte is poured on the hydrogel electrode, polymerized at room temperature for 2 to 5 minutes, and then another hydrogel electrode is attached and polymerized at room temperature for 10 to 12 hours to obtain a fully gel flexible supercapacitor.

2. The preparation method according to claim 1, characterized in that: The average size of the silver lignin nanoparticles in the silver lignin dispersion is 100 to 1000 nanometers.

3. The preparation method according to claim 1 or 2, characterized in that: In the precursor, the mass ratio of nano-hydroxyapatite to acrylamide is 1:5, and the mass ratio of the silver lignin nanoparticle dispersion to acrylamide is 1:

2.

4. The preparation method according to claim 1, characterized in that: The crosslinking agent, initiator and carbon nanotube dispersion are added to the prepolymer, wherein the mass ratio of the crosslinking agent to the acrylamide monomer is 3:1000, the mass ratio of the initiator to the acrylamide monomer is 3:250, and the mass ratio of the carbon nanotube to the acrylamide monomer is 1:

5.

5. The preparation method according to claim 4, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is any one of ammonium persulfate, potassium persulfate, and sodium persulfate.

6. The preparation method according to claim 1, characterized in that: The prepolymer of the hydrogel electrolyte is obtained by adding a crosslinking agent, an initiator and zinc chloride to the precursor, wherein the mass ratio of the crosslinking agent to the acrylamide monomer is 3:1000, the mass ratio of the initiator to the acrylamide monomer is 3:500, and the mass ratio of the acrylamide monomer to the zinc chloride is 1:

5.

7. The preparation method according to claim 6, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is any one of ammonium persulfate, potassium persulfate, and sodium persulfate.

8. A low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion prepared by the preparation method according to any one of claims 1 to 7.

9. Application of the low-temperature resistant all-gel flexible supercapacitor with strong interface adhesion performance as claimed in claim 8 in a flexible energy storage system.